Government support for revitalizing performance of tourism MSMEs: A resource advantage theory perspective - Munasingha, Prabodya; Ranasinghe, Ruwan; Ranathunga, Dinushi; Pattiyagedara, Shashika (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: The study aims to investigate the impact of Government Support on revitalizing the Environmental and Financial Performance of Tourism MSMEs with the Resource Advantage theory perspective. Methodology/approach: Data were collected from 384 TMSMEs through a snowball sampling technique using a self-administered structured questionnaire. Three multiple linear regression models were constructed to investigate the impact of Government Support as an independent variable on performance as a dependent variable, and the Statistical Package for Social Sciences (SPSS) was employed to analyze the data. Results/findings: The results indicate that both Government Financial (GFS) and Non-Financial Support (GNFS) significantly influence the financial and environmental performance of TMSMEs at a 5% level. Moreover, GFS shows a slightly high impact on financial performance GNFS, although both supports show a significant impact on revitalizing the performance of businesses in emerging economies. Conclusion: The study concludes that government financial and non-financial support are critical determinants of tourism MSME performance. Strengthened support not only enhances financial viability but also fosters environmental accountability, aligning with the principles of sustainable development. Limitations: The study focused on TMSMEs in selected emerging tourism regions of Sri Lanka, a least-developed economy, using a quantitative approach. Business performance was assessed through subjective measures due to owners' reluctance to disclose financial data. Contribution: The study contributes to R-A theory by highlighting how government support strengthens firms' resource capabilities, leading to superior performance. It also facilitates policymakers, tourism entrepreneurs, and regulators in fostering regional development by revitalizing TMSMEs, reducing socio-economic disparities, and increasing per capita income.